The Regulation of Non-Fungible Tokens as Fiduciary Security Objects - Al-Ghifari, Muhammad Farhan; Qamariyanti, Yulia (Multidiscience : Journal of Multidisciplinary Science, 2025)
Non-fungible tokens (NFTs) have the potential to serve as fiduciary collateral in Indonesia. As a blockchain-based innovation, NFTs enable the unique representation and transfer of digital asset ownership. Under Indonesia’s Fiduciary Security Law, NFTs qualify as fiduciary collateral objects since they are classified as intangible assets. This study examines copyright protection for NFTs in the context of fiduciary collateral, along with the legal and technical challenges in their implementation. Key obstacles include the lack of specific regulatory frameworks, insufficient blockchain infrastructure, and limited public understanding of NFTs as fiduciary collateral. Consequently, there is a need for comprehensive regulations and the establishment of oversight institutions to ensure transactional legality and security.Such regulatory measures are expected to facilitate the use of NFTs as fiduciary collateral, enhance public trust, and promote the growth of a blockchain-based digital ecosystem in Indonesia.